Evaluation of psychological distress is essential for patients with locally advanced breast cancer prior to neoadjuvant chemotherapy: baseline findings from cohort study - Majid Omari; Lamiae Amaadour; Btissame Zarrouq; Yazeed A. Al-Sheikh; Achraf El Asri; Salima Kriya; Sara Nadi; Zineb Benbrahim; Nawfel Mellas; Karima El Rhazi; Mohammed El Amine Ragala; Jaouad El Hilaly; et al. (BMC, 2023)
Abstract Background patients with locally advanced breast cancer (LABC) are often treated by neoadjuvant chemotherapy (NACT). This study aims to determine the prevalence of psychological distress and their sociodemographic and clinical factors in patients recently diagnosed with LABC and before NACT. Methods: A total of 209 LABC patients without metastatic localization were recruited between 2021 and 2022 in the oncology hospital at Fez. A structured questionnaire and the Hospital Anxiety and Depression Scale were used. A descriptive analysis and linear model were performed. Results: a mean age of participants was 47.43 ± 9.45 years. The prevalence of depression, anxiety and psychological distress among participants was 59.62% (95% CI: 52.61-33.34), 47.85% (95% CI: 40.91-54.85), and 65.07 (95% CI: 58.19-71.52) respectively. Depression was associated to age (< 50 years) (AOR = 2.19; 95% CI = 1.13-4.23) and health insurance (AOR = 3.64; 95% CI: 1.18-11.26). Anxiety was associated to age (< 50) (AOR = 2.21; 95% CI: 1.18-4.13) and right breast cancer (AOA = 2.01; 95% CI: 1.11-3.65). Psychological distress was associated to chronic illness (AOR = 2.78; 95% CI: 1.32-5.85) and lymph node status (AOR = 2.39; 95% CI: 1.26-4.57). Conclusions: Based on the high prevalence of depression and anxiety it appears opportune to treat psychological distress among LABC patient candidates for NACT. Each psychological intervention should take into account sociodemographic and clinical factors found associated in our study. Psychological therapeutic interventions are crucial for LABC patients as early as the time of diagnosis and through subsequent steps in NACT to improve their overall mental health.